Regulatory properties of araC(c) mutants in the L-arabinose operon of escherichia coliB/r. - MacInnes, K R (1978)
Merodiploids containing a high-constitutive and a low-constitutive araC(c) allele were assayed for constitutive expression of the ara operon. Low-constitutive araC(c) alleles either were unable to repress the constitutive rate of ara operon expression exhibited by by high-constitutive araC(c) alleles or achieved a partial repression of the high-constitutive rate of operon expression. Either mutation to a low-constitutive araC(c) mutant resulted in a partial or complete loss of repressor function, or subunit mixing between the two araC(c) mutant proteins resulted in a partial or complete dominance of the high-constitutive araC(c) allele. Five of the six araC(c) alleles tested allowed a partial induction of the ara operon in cya crp background. In general, a higher level of ara operon induction was achieved in the cya crp background by high araC(c) alleles than by low araC(c) alleles. Furthermore, several araC(c) mutants exhibited decreased sensitivity to catabolite repression, particularly in the presence of inducer. The results suggest a model in which certain araC(c) gene products can achieve ara operon induction in the presence of either arabinose (inducer) or catabolite activator protein-cyclic adenosine monophosphate, whereas the wild-type araC gene product requires the presence of both of these factors for operon expression.